Beta oscillations precede joint attention and correlate with mentalization in typical development and autism. (April 2019) - Soto-Icaza, Patricia; Vargas, Lorena; Aboitiz, Francisco; Billeke, Pablo
Abstract: A precursor of adult social functioning is joint attention (JA), which is the capacity to share attention on an object with another person. JA precedes the development of the capacity to attribute mental states to others (i.e., mentalization or theory of mind). The neural mechanisms involved in the development of mentalization are not fully understood. Electroencephalographic recordings were made of children while they watched stimuli on a screen and their interaction with the experimenter was assessed. We tested whether neuronal activity preceding JA correlates with mentalization in typically developing (TD) children and whether this activity is impaired in children with autistic spectrum disorder (ASD) who evidence deficits in JA and mentalization skills. Both groups exhibited JA behavior with comparable frequency. TD children displayed a higher amplitude of negative central (Nc) event-related potential preceding JA behavior (∼500 msec after stimuli presentation), than did the ASD group. Previous to JA behavior, TD children demonstrated beta oscillatory activity in the temporoparietal region, while ASD children did not show an increase in beta activity. In both groups, the beta power correlated with mentalization, suggesting that this specific neuronal mechanism is involved in mentalization, which used during social interaction.